WEBSITE PROFIL BERBASIS CLOUD COMPUTING DENGAN MODEL LAYANAN SOFTWARE AS A SERVICES - Marhayu, Marhayu; Purwanti, Ruth Estheriana (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Website with Cloud Computing is a service that can allow users or companies to performelectronic access to information . Cloud Computing is currently very favorable in terms ofpromotion / introduce information especially in education . With the application of thesetechnologies will be constructed a " Implementation of Cloud Computing To Wesbsite PrimarySchool Profiles With Software As A Service Model Services ( SaaS ) " which serves as one of themeans that are used as a medium to share information about what 's in elementary school .This website uses waterfall system development methods according to Pressman with itsphases starting from the analysis in which designed using the method of data collection and 4models using UML diagrams as the design of the system , usecase diagram , aktivity diagrams ,class diagrams , and sequence diagrams and ERD as database design , the second stage of thedesign phase in which there is design using tables , sitemap design and the design of inter- face ,the third stage is the stage in which explains the code language used for the creation of programssuch as PHP and HTML languages , and the final stage of the testing phase using a black box .On the Website Service software as a service ( SaaS ) for Primary School Profile providesseveral features that can be easily managed by users or members that add , modify , delete , andcan be easily downloaded images as the gallery website content ( facilities and activities ) ,employee data , information ( news ) , and the profile of its own members